Exploring the Determinants of Performance Based on Human Resources Management and Work Motivation - Khasanah, Muthi’atul; Qusaeri, Muammar Afif Al; Khasbulloh, M. Wahab; Wiliyanto (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to analyze the influence of human resources management and work motivation on employee performance at CV Guna Dharma Klaten. This study used a quantitative approach with a survey method. Respondents consisted of 97 CV Guna Dharma Klaten employees selected using a census technique. The research instrument was a questionnaire measured using a 5-point Likert scale. Data were analyzed using Partial Least Squares (PLS) using SmartPLS 4 software to test the direct relationship between variables. The results indicate that human resources management and work motivation have a significant positive effect on employee performance. The practical implication of this study is the need for an HRM strategy that emphasizes creating work motivation to strengthen employee engagement, thereby achieving sustainable performance improvement. This research contributes to the development of a conceptual model in the field of human resource management to understand the mechanisms for improving employee performance.